In situ CUTANEOUS CELLULAR IMMUNE RESPONSE IN DOGS NATURALLY AFFECTED BY VISCERAL LEISHMANIASIS - Rossi, Claudio Nazaretian; Tomokane, Thaise Yumie; Silva Batista, Luis Fabio da; Marcondes, Mary [UNESP]; Larsson, Carlos Eduardo; Laurenti, Marcia Dalastra (Inst Medicina Tropical Sao Paulo, 2016)
Thirty-eight dogs naturally affected by visceral leishmaniasis were recruited in Aracatuba, Sao Paulo State, Brazil - an endemic area for visceral leishmaniasis. The animals were distributed into one of two groups, according to their clinical and laboratory features, as either symptomatic or asymptomatic dogs. Correlations between clinical features and inflammatory patterns, cellular immune responses, and parasitism in the macroscopically uninjured skin of the ear were investigated. Histological skin patterns were similar in both groups, and were generally characterized by a mild to intense inflammatory infiltrate in the dermis, mainly consisting of mononuclear cells. There was no difference in the number of parasites in the skin (amastigotes/mm(2)) between the two groups. Concerning the characterization of the cellular immune response, the number of positive inducible nitric oxide synthase (iNOS(+)) cells was higher in the dermis of symptomatic than in asymptomatic dogs (p = 0.0368). A positive correlation between parasite density and macrophages density (p = 0.031), CD4(+) T-cells (p = 0.015), and CD8(+) T-cells (p = 0.023) was observed. Furthermore, a positive correlation between density of iNOS+ cells and CD3(+) T-cells (p = 0.005), CD4(+) T-cells (p = 0.001), and CD8+ T-cells (p = 0.0001) was also found. The results showed the existence of a non-specific chronic inflammatory infiltrate in the dermis of dogs affected by visceral leishmaniasis, characterized by the presence of activated macrophages and T-lymphocytes, associated to cutaneous parasitism, independent of clinical status.
Keywords: Canine visceral leishmaniasis; Cutaneous lesion; Histopathology; Cellular immune response